Factors affecting consumers' acceptance towards electronic payment system: case of a government land and district office / Mohamad Azwan Md Isa, Ferri Nasrul and Suhana Mohamed - Md Isa, Mohamad Azwan; Nasrul, Ferri; Mohamed, Suhana (Universiti Teknologi MARA, Perlis, 2018)
Electronic payment system (e-payment) is a new trending applied at government offices in Malaysia. Among the main reasons to introduce and apply this platform are to increase the efficiency by reducing the number of customers' queue, to minimize the risk of cash shortage and fraud by operating staff. Even though the implementation of the e-payment system has been for more than a decade and the encouragement has been done regularly to use the system, but there is still lack of acceptance and usage among the public. Hence, this paper aims to investigate the factors affecting the consumers' acceptance towards the usage of e-payment system. Employing the simple random sampling, we distribute questionnaires to 100 quit rent payers at Land and District office in Johor, Malaysia. Four variables are identified; performance expectancy, effort expectancy, social influence and facilitating conditions. We found that all the four variables have positive relationships with consumers' acceptance towards using the e-payment system. However, based on the multiple regression results, only the facilitating conditions and effort expectancy are found to have significant influences on the consumers' acceptance to use e-payment system. The results indicate that there are still shortcomings in the e-payment system in facilitating the users' transactions. The findings are beneficial to the government offices or agencies to continuously improve and upgrade their e-payment systems in effort to deliver the best and most efficient services as expected by the public users.